2017
DOI: 10.1016/j.ijid.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of upper respiratory infections using a new multiplex PCR assay compared to conventional methods during the influenza season in Taiwan

Abstract: The FilmArray assay facilitates urgent testing and laboratory surveillance for common viral and bacterial respiratory pathogens. This study demonstrated the use of a highly sensitive assay using clinical samples that is feasible for application worldwide. This may lead to an increased rate of diagnosis of viral infections and to improved patient outcomes, and in particular to a reduction in the overuse of antibiotics and antivirals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…This present study is one of the several that have examined the application of FA‐RP in Asia . Compared with other published studies, our study focused on adults with more severe pneumonia conditions, and to the best of our knowledge, it is the only study that has covered two consecutive pandemic seasons.…”
Section: Discussionmentioning
confidence: 99%
“…This present study is one of the several that have examined the application of FA‐RP in Asia . Compared with other published studies, our study focused on adults with more severe pneumonia conditions, and to the best of our knowledge, it is the only study that has covered two consecutive pandemic seasons.…”
Section: Discussionmentioning
confidence: 99%
“…ese results suggest that the FARP assay may serve as a rapid alternative to routine testing for those targets that are included on the multiplex panel. Furthermore, FARP testing may play an important role in patient management decisions, including infection control and antimicrobial stewardship [11]. If a bacterial pathogen is detected, broad-spectrum coverage could be modified to offer more specific antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 99%
“…If a bacterial pathogen is detected, broad-spectrum coverage could be modified to offer more specific antimicrobial therapy. In contrast, if a viral pathogen is detected and bacterial cultures remain negative, it may be prudent to discontinue antibiotics and initiate targeted antiviral therapy [11]. Bronchoscopy with BAL is routinely ordered in ICH patients at our 2), methicillin-resistant Staphylococcus aureus (n � 1), Serratia marcescens (n � 1), Pneumocystis jirovecii (n � 1), Scopulariopsis (n � 1), Bordetella bronchiseptica (n � 1), Haemophilus influenzae (n � 1), Stenotrophomonas maltophilia (n � 1), Proteus mirabilis (n � 1), Mycobacterium avium complex (n � 1), and Histoplasma capsulatum (n � 1) (three patients had more than one pathogen detected); c organisms recovered/detected: Mycobacterium avium complex (n � 4), Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of influenza antigen test was reported as 62.3% [5]. Additionally, in the study comparing the FilmArray RP and conventional culture, the former identified Influenza viruses in all 24 influenza culture-positive cases, with a predictive value of 100% [13]. Accordingly, the result of influenza antigen test in the six patients might be false-negative.…”
Section: Discussionmentioning
confidence: 97%